Modelo para controle da anemia infecciosa equina na região Amazônica - Cláudia Fideles Resende (2021)
The Marajoara and Puruca horses live in the Marajó Island (Pará), originated in the region and adapted to the climatic adversities of the Amazon biome, as well as other introduced and crossbred breeds, many of which are raised in feral conditions. It is estimated that roughly 40% of the equids on the island are seropositive for equine infectious anemia (EIA), caused by the Equine infectious anemia virus (EIAV). Due to absence of effective treatment and vaccines, the control of EIA occurs by breaking the transmission cycle, which occurs horizontally, iatrogenic or by hematophagous insects. There is evidence that foals are more resistant to EIAV infection, even in regions with high vector density, such as the Brazilian Amazon. Therefore, the aims of this study were: (1) to establish an EIA control methodology in a representative property of the Marajó Island, in Soure municipality, through the association of diagnostic tests (AGID and ELISApgp45) and segregation of seropositive equids; and (2) determine the transmissibility of the EIAV to foals borned and maintained with seropositive feral mares until natural weaning. It was observed a significant prevalence decrease of EIA within herd, that reduced from 27.09% to 0.36% at the end of two years of the study, while the foals had a low infection rate, only 7.14% of the group became seropositive in the evaluated period. The results obtained show that it is possible to control the spread of EIA in areas with high prevalence through periodic monitoring and segregation of positives, as well as obtaining negative foals born from positive mares even after weaning under natural conditions in a region with high density of vectors.